Application of vertical transposition flap in closure for large facial soft tissue defects in children - Feng, Rui; Chen, Jigang; Wang, Yining (Frontiers in Pediatrics, 2023)
Background: While transposition flap is widely used for the repairs of facial defects, few studies has reported its application among children with large defects. In this study, we aimed to investigate the surgical techniques and principles in different locations on face of vertical transposition flap in children. Methods: We retrospectively reviewed our hospital database and identified children who were treated with vertical transposition flap for large facial defects between January 2014 and December 2021. Information was collected including patients’ demographics, location and dimension of the lesion, surgical procedure, additional surgeries, complications, and outcomes. Results: A total of 122 patients (77 boys, 63.1%) were included in this study. The average age for participants was 3.7 years (3 months to 9 years). One hundred and four (85.3%) patients had melanin nevus and 18 (14.8%) had sebaceous nevus. The average size of defects was 5.9 cm2 (ranging from 1.5-16.5 cm2). Ten patients (8.2%) suffered from dermal layer or full-thickness necrosis in the distal part of their flaps，They all recovered after conservative treatment and there were noticeable scars at discharge. Five patients(4.1%) had slight traction of the mouth and eyelid，all recovered about 2 week after surgery. An acceptable cosmetic outcome was achieved for all the patients at last time follow-up. Conclusions: Repairing large facial defects with vertical transposition flap is effective in Children, especially on forehead, cheek and mandible. However, this technique is far from perfect. Careful selection of appropriate patients and flap design might be needed.